2020
DOI: 10.4236/fns.2020.111006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Physico-Chemical Indices of Frying Oils Used by Attieké-Fish Sellers in Daloa (Mid-West of Côte d’Ivoire)

Abstract: The purpose of this article is to compare the quality of three edible oils derived from palm oil in Daloa's city. The methodological approach of the article includes, on the one hand, a field survey determining the most used oils and the number of frying carried out by the attieké-fish sellers. On the other hand, the physico-chemical parameters (refractive index, iodine index, saponification index, acid index and peroxide index) of these oils were determined. As a result, the most used oils are A, B and C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
1
1
Order By: Relevance
“…This indicated that the unsaturated part of the oil was removed and more saturation was formed during frying. The result of this study is not correlated with the previous study report and stated that the RI increase is believed to be related to the high saturated fatty acid content and the non-hydrogenation of palm oil, making it less resistant to heat [ 55 ]. The deviation might be due to the reaction conditions and the frying cycle.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This indicated that the unsaturated part of the oil was removed and more saturation was formed during frying. The result of this study is not correlated with the previous study report and stated that the RI increase is believed to be related to the high saturated fatty acid content and the non-hydrogenation of palm oil, making it less resistant to heat [ 55 ]. The deviation might be due to the reaction conditions and the frying cycle.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of this study were in close agreement with the previous study report and stated that at the elevated cooking temperature of 350 °C, the SV increased to 250 mg of KOH per 100 g of oil and produce more FFA during frying [ 54 ]. Furthermore, the results of these studies are supported by the previous similar study report and state that a high SV results in a high level of short-chain fatty acids and higher glycerol content [ 55 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation